Los tipos sociales en las novelas de Azorín. el ‘alma nacional’ de los pueblos abúlicos - Cuvardic García, Dorde (2013)
Certain social rural types, representative of the 'Spanish soul', predominates in the apathetic villages of Azorin ́snovels. The most common of these are the nun, the farmer, and the intellectuals (who, after struggling unsuccessfullyin modern cities, retire to the space of apathetic/ lethargic/indolent cities and towns), the inventors of useless artifacts,the priests, elder female devotees, and representatives of vanishing occupations... As symbols, they possess an ambi-valent semantics: on the one hand, they synthesize the ' Spain problem', that is, the Iberian nation inability to solve itscollective problems, and secondly, if explored carefully, the values ​​ these social types will provide the possibilitiesofto solve the moral and social stagnation of the country. Only some of these social types appear in the topos of thedead city at a European level; such is the case of the nun which acquires a partially different semantics to thatoffered by Azorin and other writers of the 98 ́s Generation.